The management of oral erythema multiforme in juvenile patient - Diah Savitri Ernawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Erythema multiforme is an acute inflammatory disease of the skin and mucous membranes that causes a variety of the skin lesionhence the name ‘multiforme’.The oral mucosa looks severely inflamed, but the feature are non specific and usually a biopsy is required in order to confirm the diagnosis. Cracked, bleeding, Crusted, swollen and ulcers of the lips is very characteristic of erythema multiforme, and lip involvement may cause significant morbidity. EM is assumed as an immune complex disorder which rises as a result of an immune response to an external agent such as herpes simplex virus or various drugs. We reported: 14-year girl, complained she suffered from painful oral ulceration for one week. One weeks advance the patient received a treatment of paracetamol and paramex for febris, headache and cough. Clinical examination of the skin showed no signs of cutaneous involvement. Other site such as the conjunctival, and genital were also free of lesions. The patients had several red-based superficial erosions on the upper and lower lips accompanied by crusting and bleeding. Intra oral findings showed multiple irregular erosions, ulcers and intense erythematous areas, mainly on the labial mucosa. The clinical diagnosis of EM was concluded by anamnesis and clinical appearance, with differential diagnosis of secondary herpes infection (herpes labialis) and pemphigus vulgaris. Systemic and topical corticosteroid therapy is frequently used to treat EM Although it may partially suppress the disease. Objective: This report explains and describes the management of patients with EM which may help dentists to determine an accurate diagnosis to avoid further complication and to give medical intervention to the disease. Conclusion: Early recognition of this disease may prevent delayed diagnosis and incorrect treatment.